Usage of group AHP approach in karate agility test selection - Marjani, Mohammad Ebrahim; Soh, Kim Geok; Majid, Mojahed; Omar Fauzee, Mohd Suffian; Abdullah, Nur Surayyah Madhubala; Abu Bakar, Mohd Rizam (Universiti Putra Malaysia Press, 2012)
Karate is one of the most popular martial art styles in the world as well as a popular sport in Iran. Successful performance in karate requires a high level of agility that enables the karateka (karate player) to avoid the opponent’s attacks, and to assume optimal position for efficient performance of karate techniques. In order to measure agility in karatekas, karate coaches make use of general and available agility tests. However, there are many agility tests but coaches need to know which one is the best test for karatekas. Analytic Hierarchy Process (AHP). Data were collected from six karate experts’ opinions in order to weight and rank agility tests specifically to select the best agility test. AHP approach allows the weight of each criterion from each expert to be computed in geometrical mean. As a result, based on experts’ opinion and using Group AHP approach, the best validated agility test for Karate is Illinois test. This paper describes the usage of the group AHP approach in selecting the most appropriate agility test for karate. It discusses some of the advantages and disadvantages of using this approach. It also suggests how the approach can be used in sports research.